Effect of mitoquinone on liver metabolism and steatosis in obese and diabetic rats - Brian D. Fink; Liping Yu; Lawrence Coppey; Alexander Obrosov; Hanna Shevalye; Robert J. Kerns; Mark A. Yorek; William I. Sivitz (Pharmacology Research & Perspectives, 2021)
Abstract Previous work by ourselves and others showed that mitoquinone (mitoQ) reduced oxidative damage and prevented hepatic fat accumulation in mice made obese with high‐fat (HF) feeding. Here we extended these studies to examine the effect of mitoQ on parameters affecting liver function in rats treated with HF to induce obesity and in rats treated with HF plus streptozotocin (STZ) to model a severe form of type 2 diabetes. In prior reported work, we found that mitoQ significantly improved glycemia based on glucose tolerance data in HF rats but not in the diabetic rats. Here we found only non‐significant reductions in insulin and glucose measured in the fed state at sacrifice in the HF mice treated with mitoQ. Metabolomic data showed that mitoQ altered several hepatic metabolic pathways in HF‐fed obese rats toward those observed in control normal chow‐fed non‐obese rats. However, mitoQ had little effect on pathways observed in the diabetic rats, wherein diabetes itself induced marked pathway aberrations. MitoQ did not alter respiration or membrane potential in isolated liver mitochondria. MitoQ reduced liver fat and liver hydroperoxide levels but did not improve liver function as marked by circulating levels of aspartate and alanine aminotransferase (ALT). In summary, our results for HF‐fed rats are consistent with past findings in HF‐fed mice indicating decreased liver lipid hydroperoxides (LPO) and improved glycemia. However, in contrast to the HF obese mice, mitoQ did not improve glycemia or reset perturbed metabolic pathways in the diabetic rats.